2008
DOI: 10.1098/rstb.2008.0087
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility, evolution and the kuru epidemic

Abstract: The acquired prion disease kuru was restricted to the Fore and neighbouring linguistic groups of the Papua New Guinea highlands and largely affected children and adult women. Oral history documents the onset of the epidemic in the early twentieth century, followed by a peak in the mid-twentieth century and subsequently a well-documented decline in frequency. In the context of these strong associations (gender, region and time), we have considered the genetic factors associated with susceptibility and resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…If the different villages that experienced the travelling wave at different times comprised individuals of different genotype frequencies prior to the epidemic, our conclusions would be affected. However, recent genotyping of young modern Fore and young individuals from the East Highland Papua New Guinea region that was not affected by kuru did not show a significant deviation from the 25/50/25% MM/MV/VV genotype frequency [16], suggesting that it was unlikely that there were differences in the genotype frequencies between villages initially. Additionally, there is evidence that the age of onset of kuru is strongly correlated with the probability that the patient is heterozygote [12,33].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…If the different villages that experienced the travelling wave at different times comprised individuals of different genotype frequencies prior to the epidemic, our conclusions would be affected. However, recent genotyping of young modern Fore and young individuals from the East Highland Papua New Guinea region that was not affected by kuru did not show a significant deviation from the 25/50/25% MM/MV/VV genotype frequency [16], suggesting that it was unlikely that there were differences in the genotype frequencies between villages initially. Additionally, there is evidence that the age of onset of kuru is strongly correlated with the probability that the patient is heterozygote [12,33].…”
Section: Discussionmentioning
confidence: 92%
“…genotypes was 50 per cent [16]. All genotype models described the kuru mortality incidence data equally well, yielding similar corrected Akaike information criteria (AICc) values.…”
Section: Epidemiological Mechanism Of Host Resistancementioning
confidence: 86%
See 1 more Smart Citation
“…Studies that examined the molecular genetic basis of susceptibility to kuru found that homozygotes for methionine at codon 129 were overrepresented in the younger age group, while valine homozygotes and heterozygotes were overrepresented in the much older age group, and survivors were almost never carried homozygotes for methionine at this position (Liberski, 2013). Heterozygosity at this codon was associated with older patients and with longer incubation times (Mead et al, 2008). It is thought that heterozygotes were protected from disease by the more difficult interactions between the protein heterodimers, while the homologous protein-protein interactions made homozygotes more susceptible to disease (Palmer et al, 1991).…”
Section: Zoonotic Transmissionmentioning
confidence: 99%
“…At the beginning, it was demonstrated that 2 kuru cases were 129 Met Met [ 149 ]. Further studies found that individuals of 129 Val Val and 129 Met Val genotype were susceptible to kuru, but those of 129 Met Met genotype were overrepresented in the younger age group while those of 129 Val Val 129 Met Val were overrepresented in much older age group [ 53 , 95 , 150 , 151 , 152 , 153 ]. In contrast, those people who survived the epidemic were characterized by almost the total absence of 129 Met Met homozygotes.…”
Section: Genetics and Molecular Biology Of Kurumentioning
confidence: 99%